2020
DOI: 10.1111/1440-1681.13374
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and incident atrial fibrillation: A systematic review and dose–response meta‐analysis

Abstract: Atrial fibrillation is the most common cardiac arrhythmia in clinical practice, with increased cardiovascular morbidity and mortality worldwide. 1 Although multiple risk factors, including cardiovascular and non-cardiovascular risk factors have been identified, the pathophysiology of atrial fibrillation remains incompletely understood. Over 40% of the risk attributed to atrial fibrillation still remains unexplained after accounting for established risk factors. Serum uric acid (SUA) is an end product of purine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…The results of Tamariz et al and Zhang et al are consistent in principle with the meta-analysis by Xu et al [ 18 ]. The latest research results based on the analysis of 11 studies (over 500,000 patients in total and nearly 7000 cases of AF) showed that the relationship between SUA concentration and the risk of AF is linear, that the risk increases significantly even at SUA concentrations above 5 mg/dL, and that for every additional 1 mg/dL it increases by 21% (RR 1.21; 95% CI 1.12–1.32; I2 = 78%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Tamariz et al and Zhang et al are consistent in principle with the meta-analysis by Xu et al [ 18 ]. The latest research results based on the analysis of 11 studies (over 500,000 patients in total and nearly 7000 cases of AF) showed that the relationship between SUA concentration and the risk of AF is linear, that the risk increases significantly even at SUA concentrations above 5 mg/dL, and that for every additional 1 mg/dL it increases by 21% (RR 1.21; 95% CI 1.12–1.32; I2 = 78%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increased focus has been given to the possible mechanism by which hyperuricemia causes AF. Similarly, the link between hyperuricemia and other conditions such as hypertension, metabolic syndrome, diabetes mellitus, and chronic kidney disease has been reported (9)(10)(11). Uric acid [UA; 7,9-hihydro-1H-purine-2,6,8(3H)-trione; C5H4N4O3; molecular weight of 168.11 Da] is a heterocyclic organic compound and an end product of purine metabolism in humans.…”
Section: Introductionmentioning
confidence: 97%
“…Hyperuricemia can increase the risk of AF [39]. Numa et al [40] described that the serum uric acid level was associated with thromboembolic risk on transesophageal echocardiography in patients with NVAF at low-intermediate risk according to stratification by clinical risk factors.…”
Section: Uricemiamentioning
confidence: 99%